Boxholders at the Opera: Identity and Functions at the Theatres of the ex-Serenissima - Scuderi, Cristina (Musicologica Olomucensia, 2023)
This article sheds light on the identity and functions of the boxholders in the coastal theatres of part of the former Venetian republic at the turn of the 20th century, investigating which social categories were represented among them and in what economic terms of "ownership" they were related to the theatre. The boxholders held regular meetings. How were their assemblies organised? What was discussed? Those who paid a social fee for the opera season had a say in the works to be performed, the endowment to be granted to the impresario, and even the cost of admission tickets to the theatre. There were many disputes that could arise from these collective decisions; one event, however, managed to unify the intentions of the boxholders, namely what happened with the death of Giuseppe Verdi. There was a common intent to name many of the coastal theatres after the composer: was it just a tribute to a great artist or perhaps the desire to affirm the italianita of the shareholders in an area that perceived pressure from Croatian nationalists and the growing demands of the Habsburg monarchy for a "germanisation" or "slavicisation" of the territory?
Keywords: Boxholders; Shareholders; 19th and 20th Century Opera; Social Theatres